Semantic Wikipedia. - Krötzsch, M; Vrandecic, D; Völkel, M; Haller, H; Studer, R (2007)
Wikipedia is the world's largest collaboratively edited source of encyclopaedic knowledge. But in spite of its utility, its content is barely machine-interpretable and only weakly structured. With Semantic MediaWiki we provide an extension that enables wiki-users to semantically annotate wiki pages, based on which the wiki contents can be browsed, searched, and reused in novel ways. In this paper, we give an extended overview of Semantic MediaWiki and discuss experiences regarding performance and current applications. © 2007 Elsevier B.V. All rights reserved.